The Influence of Marketing Mix Strategy on Customer Loyalty at Alluree Coffee Manado - Montolalu, Marsha Magdalena; Pio, Riane Johnly; Mukuan, Danny (Productivity, 2025)
This study aims to analyze the influence of marketing mix strategies, consisting of product, price, promotion, and place, on customer loyalty at Alluree Coffee Manado. The research employed a quantitative approach using multiple linear regression analysis. The findings indicate that, partially, product and promotion have a significant effect on customer loyalty, whereas price and place do not show a significant impact. However, the four marketing mix elements jointly have a significant influence on customer loyalty. These results highlight that product quality and effective promotional activities are the key determinants of customer loyalty, while the other elements serve as supporting components in an integrated marketing strategy. The study suggests that Alluree Coffee’s management should prioritize improving product quality and enhancing promotional creativity to strengthen customer loyalty.